Cluster folding model analysis of the 7Be+28Si elastic scattering in the near-barrier. (1st February 2023) - Anwar, M; Hemmdan, A
Abstract: In the framework of the optical model, the elastic scattering of the radioactive projectile 7 Be on the 28 Si target at four energies near the Coulomb barrier has been analyzed. The cluster folding model is used to determine the real part of the nuclear optical potential. For comparison, two microscopic optical potentials have been generated using the DDM3Y effective NN interaction based upon two different forms for 7 Be density distribution. All the obtained real potentials, in conjunction with phenomenological Woods-Saxon imaginary parts, have successfully reproduced the elastic scattering angular distributions over the measured angular range. The energy dependence of the real and imaginary strengths that are produced by the best-fit of the experimental data was examined. Neither the usual threshold anomaly nor the breakup threshold anomaly can be observed at the considered energy range. The obtained cross sections have been reduced and compared with earlier theoretical and experimental data of 7 Li on the same target near the Coulomb barrier.